The effect of a coping program on mothers' grief following perinatal deaths - Leila Nournorouzi; Roghaiyeh Nourizadeh; Sevil Hakimi; Khalil Esmaeilpour; Leila Najmi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Mother-child attachment is formed from early stages of pregnancy and peaks in the second trimester and continues until after childbirth. The fetal or neonatal death as a tragic event could lead to the grief experience among parents, especially mothers. The present study aimed to determine the effect of a coping program on mothers' grief following perinatal deaths. MATERIALS AND METHODS: This trial study was performed on 56 women with the experience of perinatal death during the last 1-3 months with a score of Perinatal Grief Scale (PGS) ≥91, who were referred to the health centers of Tabriz, Iran, from September 2020 to June 2021. Participants were randomly assigned into the intervention and control groups through stratified blocking on the basis of the stillbirth and neonatal death using Random Allocation Software with a block size of 4 and 6 with a ratio of 1:1. The intervention group received a coping program individually during three sessions, once a week for 45-60 min. Data collection tools included the demographic and obstetric characteristic questionnaire and PGS. The data were analyzed using SPSS24. The groups were compared through t-test, and ANCOVA after adjusting the effect of baseline score. RESULTS: Prior to coping program, the mean standard deviation of the grief total score was 108.32 (14.31) in the intervention group and 107.92 (6.65) in the control group (P = 0.89). After coping program, the mean of the grief total score was 82.28 (16.72) in the intervention group and 101.05 (12.78) in the control group. After adjusting the effect of baseline score and stratified factors, the mean of the grief total score in the intervention group was significantly lower than that in the control group [Adjusted mean difference (AMD): −18.77, 95% confidence interval: −26.79 to − 10.75, P ≤ 0.001]. CONCLUSION: Conducting a coping program during 1-3 months after experiencing perinatal deaths is effective in reducing the mothers' grief reactions. It is recommended to evaluate the effectiveness of the same intervention after perinatal deaths for both parents with a longer follow-up period in further studies.